An Analysis of Translation Techniques in the English Version of Arrahman Surah - Farida Repelita Waty Kembaren (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
The Holy Qur’an has been translated into many languages including English. However, different translator of the Holy Qur’an produces different English version of Al-Qur’an because every translator uses different translation techniques to translate Al-Qur’an. This study aims to compare the three English versions of Arrahman surah, and describe the most dominant translation techniques used by the three translators to translate the Holy Qur’an. Translation techniques proposed by Molina and Albir (2002, p.509-511) are used to analyze the data. The data for this study are words, phrases, and clauses in the 78 verses of Arrahman surah in Arabic and its three English versions translated by Maulawi Sher ‘Ali, Dr. Muhammad TaqiudDin AlHilali and Dr. Muhammad Muhsin Khan, and Talal Itani. The result shows that there are four most dominant techniques used by the three translators in translating the Holy Qur’an; Adaptation, Amplification, Established Equivalent, and Literal Translation technique. The first and the second translator prefer to use Amplification to introduce details in brackets or footnotes, but the third translator prefers to use Established Equivalent to find a term or expression recognized (by dictionaries or language in use) as an equivalent.Keyword: Qur’an, Surah Arrahman, Technique, Translation